METHOD & IMPLEMENTATION OF DATA FLOW TO IMPROVE QoS IN MPLS NETWORK - Raman; Silki Baghla; Dr. Himanshu Monga (Applied Engineering Letters, 2016)
Quality of service (QoS) is the mechanism of the network to provide different service level to a different traffic type as business need. The main objective of this work is to improve QoS in network by reducing link load and bandwidth consumption. It uses a routing scheme that satisfies expected demand and minimized link utilization of system. It works on reliability by limited usage of bandwidth. Results are presented to demonstrate the effectiveness of system. The efficient QoS model provides better control and administration of network traffic. Solution of routing problem with help of proposed model allows providing the distribution of traffic between source- and destination-node so that delays along every path are equal.